Adaptações locais de um tesouro universal: análise comparativa de duas versões de uma enciclopédia infanto-juvenil de inícios do século XX - María Clara Ruiz (2012)
The present work aims at analyzing comparatively the first editions of Thesouro da Juventudeand El Tesoro de La Juventudencyclopedias, dated inaccurately from the 1920s decade. As well as in other various countries of the world, the translationsofThe Book of Knowledgeencyclopedia had huge editorial success in Brazil and Argentina. Although they were part of the same editorial project organized by the North American editorial company a question mark comes up to the thought of to what extentthe original encyclopedia had to change to adjust itself to different contexts. A main question made so as to understand the history of knowledge is its diffusion and the strategies and solutions found locally. Such international and inaugural venture isa remarkable case to examine the diffusion process and knowledge reappropriation. As we will observe, most part of subjects discussed mainly the ones related to Natural Sciences and technology was translated without major changes in the two versions, which contributes to universalizing knowledge produced in other places, as well as universalizingrepresentations that would influence the readers general and scientific culture adjusting. However, it is possible to observe small alterations, product of editorial decisions, either in the original version texts selection, or in the addition of other matters, more attractive and interesting to the distribution space of each version. At the same time, equivalent texts may contain different focuses, emphasis and omissions which provide each case with different perceptions in the addressing of certain themes. On the other hand, when dealing with themes such as History, Geography and Literature, the adaptations become more evident. We notice then, specially, thecentralization given to Brazilian reality in the Portuguese version, and at the same time, being the Spanish version common to many Latin American countries, the editorial decisions had to perform different adjustments so that the adaptation of the work can be more attractive to all countries in which it would be read.